2015
DOI: 10.1016/j.ydbio.2014.09.033
|View full text |Cite
|
Sign up to set email alerts
|

From classical to current: Analyzing peripheral nervous system and spinal cord lineage and fate

Abstract: During vertebrate development, the central (CNS) and peripheral nervous systems (PNS) arise from the neural plate. Cells at the margin of the neural plate give rise to neural crest cells, which migrate extensively throughout the embryo, contributing to the majority of neurons and all of the glia of the PNS. The rest of the neural plate invaginates to form the neural tube, which expands to form the brain and spinal cord. The emergence of molecular cloning techniques and identification of fluorophores like Green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 179 publications
0
35
0
1
Order By: Relevance
“…However, netrin1 transcript is also expressed by many progenitors in the VZ in the mouse spinal cord (Serafini et al, 1996), a region ubiquitously avoided by spinal axons (Figures S1A, S1B) (Butler and Bronner, 2015). To resolve the role of FP- versus VZ-derived netrin1, we have used multiple genetic approaches to determine the spatial requirement for netrin1 in the developing spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…However, netrin1 transcript is also expressed by many progenitors in the VZ in the mouse spinal cord (Serafini et al, 1996), a region ubiquitously avoided by spinal axons (Figures S1A, S1B) (Butler and Bronner, 2015). To resolve the role of FP- versus VZ-derived netrin1, we have used multiple genetic approaches to determine the spatial requirement for netrin1 in the developing spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…The spinal cord is organized into layers from its earliest genesis: Sox2 + neuroepithelial progenitors within the VZ give rise to postmitotic neurons that migrate laterally to form the mantle layer and extend axons in the lateral marginal zone (Butler and Bronner, 2015). Spinal axons can be broadly categorized by their protein complement: neurofilament (NF) is generally present in spinal axons, with Robo3 additionally being present in the commissural axons projecting towards FP at the ventral midline (Sabatier et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The nervous system consisting of the central nervous system (CNS) and the peripheral nervous system (PNS) is a complex network of nerves and specialized cells, known as neurons that regulate actions, such as cellular basis, behavior, cognition, emotion, and consciousness . To date, many studies have indicated that various diseases are caused by abnormal neuronal wiring.…”
Section: Acknowledgmentsmentioning
confidence: 99%